Endoscopic ultrasound (EUS) in differential diagnosis of neuroendocrine tumors of the gastrointestinal tract - V Yakovenko (Perioperative Medicine)
Abstract. Neuroendocrine tumors are rare tumors of the gastrointestinal tract. The differential diagnosis of neuroendocrine tumors remains poorly understood.